Challenges and Needs for Support in Managing Occupational Health and Safety from Managers’ Viewpoints - Tappura, Sari; Syvänen, Sirpa; Saarela, Kaija Leena (Nordic Journal of Working Life Studies, 2014)
Proper working conditions and successful occupational health and safety (OHS) management help organizations achieve their targets and support the quality of working life and performance. Work-related stress, conflicts, work ability issues, ill health, and other challenging OHS situations in the workplace may impede the well-being and productivity of employees. According to OHS legislation, employers are responsible for managing risks and solving problems in the work community. Challenging situations can be viewed from the perspective of efficiency, since their economic effects may be remarkable. The objective of this study is to describe the challenging OHS situations managers encounter and the support they require in these situations. The results are based on thematic interviews and inquiries with top, middle, and front-line managers in three Finnish public sector service organizations. The most challenging OHS management situations are related to the administration of work under high economic pressure and constant changes in the work community, managing employee workload and time pressures, providing feedback, facilitating collaboration, and managing conflict. The managers’ own understandings, competences, and resources, as well as organizational supports, have an effect on successful resolutions of challenging OHS management situations.